2023
DOI: 10.1111/ppa.13791
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BnNAC19 in Brassica napus enhances resistance to Leptosphaeria maculans, the blackleg pathogen of canola

Abstract: Leptosphaeria maculans is a fungal pathogen that causes blackleg disease in canola (Brassica napus), resulting in significant yield and economic losses in Canada and many parts of the world. Plant NAC transcription factors play critical roles in plant development and response to biotic or abiotic stress. In this study, we identified and characterized a BnNAC19 gene from Brassica napus. The overexpression of BnNAC19 in transgenic canola plants contributed to the improvement of seedling resistance against L. mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Except for S. sclerotiorum and clubroot disease, resistance genes associated with pests and other diseases have been less studied. For example, only a few related genes have been reported for blackleg and verticillium wilt disease (Pröbsting et al, 2020;Zou et al, 2021;Haddadi et al, 2022;Zou and Fernando, 2023). Here, we focus on an overview of S. sclerotiorum and clubroot disease resistance genes in B. napus.…”
Section: Biotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for S. sclerotiorum and clubroot disease, resistance genes associated with pests and other diseases have been less studied. For example, only a few related genes have been reported for blackleg and verticillium wilt disease (Pröbsting et al, 2020;Zou et al, 2021;Haddadi et al, 2022;Zou and Fernando, 2023). Here, we focus on an overview of S. sclerotiorum and clubroot disease resistance genes in B. napus.…”
Section: Biotic Stressmentioning
confidence: 99%
“…There are numerous traits involved in the process of plant architecture improvement, but fewer related functional gene studies have been reported. Meanwhile, studies related to waterlogging, diseases and insects, silique shattering resistance, leaf color and efficient nutrient utilization in B. napus have mostly remained at the QTL level, with a few related genes being reported (Li et al, 2014;Zhang et al, 2017b;Hu et al, 2018;Feng et al, 2020;Guo et al, 2022;Li et al, 2022b;Zou and Fernando, 2023;Yang et al, 2023a;Li et al, 2023d).…”
Section: Accelerating Functional Genomics Research Of B Napusmentioning
confidence: 99%